-6(x-4)=-4(x-8)

Simple and best practice solution for -6(x-4)=-4(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-4)=-4(x-8) equation:


Simplifying
-6(x + -4) = -4(x + -8)

Reorder the terms:
-6(-4 + x) = -4(x + -8)
(-4 * -6 + x * -6) = -4(x + -8)
(24 + -6x) = -4(x + -8)

Reorder the terms:
24 + -6x = -4(-8 + x)
24 + -6x = (-8 * -4 + x * -4)
24 + -6x = (32 + -4x)

Solving
24 + -6x = 32 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
24 + -6x + 4x = 32 + -4x + 4x

Combine like terms: -6x + 4x = -2x
24 + -2x = 32 + -4x + 4x

Combine like terms: -4x + 4x = 0
24 + -2x = 32 + 0
24 + -2x = 32

Add '-24' to each side of the equation.
24 + -24 + -2x = 32 + -24

Combine like terms: 24 + -24 = 0
0 + -2x = 32 + -24
-2x = 32 + -24

Combine like terms: 32 + -24 = 8
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4

See similar equations:

| x+(x+1)+(x+2)=-75 | | 5(-2m)+4=89 | | 2b+5p=5.2 | | 3(x-4)+68=-4 | | -r+1=-7+4r-r | | 2(3x-13)=-20 | | 3(c+2+1)=9c+3 | | 86=5x-14 | | y+6-4y-3=-30 | | 1-n=13-4n | | -5(x+3)(x+8)= | | 9x^2-18w+24=0 | | 30c=18360 | | 2(1-16a)=-2a-6(a-7) | | 6x+11=8x+13 | | 3k-7k=-9-k | | 27=2y-13 | | -(-9-6x-6y)= | | 980+n=1020 | | E=(8) | | -5=3x+8 | | -4x+8=-12+x-8-7 | | -(4x-10)+2(3x+15)= | | 4x^3+24x^2+12x-40=0 | | 6x-3y+14w-5y-4w+9x= | | 592=2L+2(5L+6) | | 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 |

Equations solver categories